SISTEM INFORMASI PONDOK PESANTREN AL-MUKHLIS KALIREJO LAMPUNG TENGAH BERBASIS WEB MOBILE - Saifudin, Irfan; Arifin, Ahmad (YHMM PUBLISHING, 2023)
Children are the responsibility of parents given by the Creator, therefore it is only right that parents should look after and supervise them, especially when parents decide to enroll their children in a boarding school. On that basis, sometimes time and long distances are usually the main obstacles for parents in obtaining information, coupled with the weak storage of data on student activities by the instructor. For this reason, the purpose of this study is to design a system that helps parents participate in monitoring their children in terms of obtaining information related to students, and this is also a form of responsibility of the boarding school, especially the instructor in providing student information to parents in real time, so that unwanted things such as late information, scattered student data or forgetting factors so that the data provided is incomplete do not happen again. The results of this study are an Android-based Student Activity Monitoring Application using qualitative research with the Design and Creation concept, while the data collection method uses Observation, interviews, and literature studies. The design method uses the Software Development Life Cycle (SDLC) method and testing this application uses the Black Box and White Box methods. The conclusion obtained from this study is that the Pantau Santri Application makes it easier for parents to obtain information about students during their stay so that parents can obtain more detailed student data.